Maternal mortality in a tertiary care centre in North India: a retrospective study - Sethi, Prachi Sarin; Sharma, Sujata; Chawla, Indu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The World Health Organization (WHO) estimates that, of 536,000 maternal deaths occurring globally each year, 136,000 take places in India. Maternal death has serious implications to the family, the society and the nation. It deprives the surviving infant of mother's care. This study was done to assess maternal mortality in a tertiary care centre in north India where large numbers of patients are referred from the peripheral centers and the rural parts. This study was done to assess the causes of maternal mortality and suggest remedial measures to reduce the same. Objective of present study was to assess the causes of maternal death over a period of one year at G.M.C Amritsar, India. Methods: A retrospective hospital based study of 22 maternal deaths over a period of 1 year from June 2012 to June 2013. The information regarding demographic profile and reproductive parameters were collected and results were analyzed. Results: Over the study period, there were 22 deaths and 7272 live births (Majority were referral from other districts all over Punjab). Most common direct cause of maternal mortality was haemorrhage and anemia was the most common indirect cause. Most maternal deaths were seen in patients from rural areas, unbooked, illiterate patients and patients from low socioeconomic status. Conclusions: Proper health education should be given to the women; early registration of antenatal cases should be done which allows for rapid diagnosis and treatment of high risk cases. Also constructing a well equipped health care facility with trained staff and prompt transport facilities for early referral can bring down the maternal mortality rate in our country.